Does phosphorus influence performance of a native hemiparasite and its impact on a native legume?. Issue 4 (25th August 2021) - Cirocco, Robert M.; Facelli, Evelina; Delean, Steven; Facelli, José M.
Abstract: Phosphorus (P) is an essential plant nutrient and can become limiting in terrestrial ecosystems where parasitic plant:host associations occur. Yet little is known on how P availability influences parasite performance and its impact on hosts. We investigated the performance of the Australian native stem hemiparasite Cassytha pubescens and its impact on the native leguminous shrub Acacia paradoxa in high or low P conditions in a glasshouse experiment. Infected plants had significantly lower total, shoot, root and nodule biomass and shoot:root ratio than uninfected plants, regardless of P supply. The significant negative effect of infection on arbuscular mycorrhizal colonisation of host roots was more severe in the high P treatment. Infection significantly decreased predawn quantum yield of A. paradoxa in low P but not high P conditions. This finding may be due to the parasite‐induced significant enrichment of aluminium in host foliage in low P but not high P treatments. A. paradoxa had significantly lower foliar phosphorus concentration [P] and nitrogen concentration in low P than high P conditions. Parasite biomass and photosynthetic performance were unaffected by P, whereas C. pubescens had significantly lower stem [P] in the low P than high P treatment. Parasite carbon isotope composition was significantly higher than that of the host, especially in low P conditions. Our results show that: (a) native parasite growth and its negative impact on growth of this native shrub was unaffected by P supply and (b) soil P conditions may have no influence on stem hemiparasite:host associations in nature.